Teacher Satisfaction with Personnel Administration Services at the South Sumatra Provincial Education Office - Jusmaryanti, Jusmaryanti; Suandi, Suandi; Daud, Faizal; Juliartha, Edwar (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
One of the activities an organization performs involves providing services to both internal units and external parties. Within an organization or institution, administration serves as a hub for the exchange of goods and services. Teacher satisfaction within the personnel administration process of the South Sumatra Provincial Education Service holds significant importance, as it can yield considerable impacts. The research employs a quantitative descriptive analysis technique with percentages to analyze data, effectively portraying and elucidating the collected data. The data analysis results reveal that teacher satisfaction with personnel administration services indicates a 54.6% overall satisfaction rate across five aspects and 30 service indicators. Among the aspects studied, the highest satisfaction level pertains to reliability, while the lowest satisfaction level belongs to empathy and assurance aspects, albeit remaining within the satisfaction range. This demonstrates that the services delivered by the Manpower Division at the South Sumatra Provincial Education Office are categorized as good, resonating with a notably high level of teacher satisfaction.